Sustainability of the whole-community project '10,000 Steps': a longitudinal study - Van Acker, Ragnar (BioMed Central, 2012)
BACKGROUND: In the dissemination and implementation literature, there is a dearth of information on the sustainability of community-wide physical activity (PA) programs in general and of the '10,000 Steps' project in particular. This paper reports a longitudinal evaluation of organizational and individual sustainability indicators of '10,000 Steps'. METHODS: Among project adopters, department heads of 24 public services were surveyed 1.5 years after initially reported project implementation to assess continuation, institutionalization, sustained implementation of intervention components, and adaptations. Barriers and facilitators of project sustainability were explored. Citizens (n = 483) living near the adopting organizations were interviewed to measure maintenance of PA differences between citizens aware and unaware of '10,000 Steps'. Independent-samples t, Mann-Whitney U, and chi-square tests were used to compare organizations for representativeness and individual PA differences. RESULTS: Of all organizations, 50% continued '10,000 Steps' (mostly in cycles) and continuation was independent of organizational characteristics. Level of intervention institutionalization was low to moderate on evaluations of routinization and moderate for project saturation. The global implementation score (58%) remained stable and three of nine project components were continued by less than half of organizations (posters, street signs and variants, personalized contact). Considerable independent adaptations of the project were reported (e.g. campaign image). Citizens aware of '10,000 Steps' remained more active during leisure time than those unaware (227 ± 235 and 176 ± 198 min/week, respectively; t = -2.6; p < .05), and reported more household-related (464 ± 397 and 389 ± 346 min/week, respectively; t = -2.2; p < .05) and moderate-intensity-PA (664 ± 424 and 586 ± 408 min/week, respectively; t = -2.0; p < .05). Facilitators of project sustainability included an organizational leader supporting the project, availability of funding or external support, and ready-for-use materials with ample room for adaptation. Barriers included insufficient synchronization between regional and community policy levels and preference for other PA projects. CONCLUSIONS: '10,000 Steps' could remain sustainable but design, organizational, and contextual barriers need consideration. Sustainability of '10,000 Steps' in organizations can occur in cycles rather than in ongoing projects. Future research should compare sustainability other whole-community PA projects with '10,000 Steps' to contrast sustainability of alternative models of whole-community PA projects. This would allow optimization of project elements and methods to support decisions of choice for practitioners.